COVID-19 outcomes in giant cell arteritis and polymyalgia rheumatica versus rheumatoid arthritis: A national, multicenter, cohort study. Issue 132 (October 2022) - Vieira, Matheus; Comarmond, Cloé; Labreuche, Julien; Mirouse, Adrien; Saadoun, David; Richez, Christophe; Flipo, René-Marc; Hachulla, Eric; Drumez, Elodie; Cacoub, Patrice; ,
Abstract: Objectives: To determine whether giant cell arteritis and polymyalgia rheumatica (GCA/PMR) represent independent risk factors for worse outcomes in COVID-19. Methods: Observational, national, French, multicenter cohort (NCT04353609) comprising patients aged ≥18 years with confirmed diagnoses of either GCA, PMR or rheumatoid arthritis (RA) having presented COVID-19; those under rituximab were excluded. Primary endpoint was COVID-19 severity in GCA/PMR patients as compared to RA. We also aimed to describe the evolution of GCA/PMR patients following COVID-19. Multinomial logistic regression models were performed, with and without adjustment on pre-specified confounding factors (i.e., age, sex, body mass index, arterial hypertension, diabetes and cardiovascular disease). Unadjusted and adjusted multinomial odds-ratio (OR/aOR) and their 95% confidence intervals (CIs) were calculated as effect size using RA as reference group. Results: Between April 15, 2020, and August 20, 2021, 674 patients [45 (6.6%) GCA, 47 (7.0%) PMR, 582 (86.4%) RA; 62.8 years, 73.2% female] were included. Compared to RA patients, those with GCA/PMR were older and more frequently presented hypertension, diabetes and cardiovascular disease. Severe COVID-19 and death occurred in 24 (26.1%) and 16 (17.8%) patients with GCA/PMR, respectively. Unadjusted analyses revealed higher odds of severe COVID-19 [OR = 3.32 (95% CI 1.89–5.83; p < 0.001)] and death [OR = 3.20 (95%CI 1.67–6.13; p < 0.001)] for GCA/PMR compared to RA. After model adjustment, these odds were attenuated. Conclusion: Patients with GCA/PMR were more likely to have severe COVID-19 and higher mortality compared to those with RA. This worse prognosis is mostly due to well known risk factors for the general population rather than vasculitis per se . Highlights: GCA/PMR compared to RA patients have more frequently severe COVID-19 and higher mortality rate. GCA/PMR worse COVID-19 outcomes are mostly due to known risk factors for the general population. Risk stratification in pandemic should continue to prioritize patients with GCA/PMR.